PELABUHAN HIJAU DALAM MENDUKUNG PEMERATAAN PEMBANGUNAN DAN PERTUMBUHAN EKONOMI WILAYAH (STUDI DESKRIPTIF DI PELABUHAN PENYEBERANGAN BAUBAU) - Satyadharma, Maudhy; Marlany Rachman, Ranno; Dahlan Sabar, Anwar; Jaya Saputra, Yusuf; Hado, Hado (JURNAL TEKNIK, 2024)
Ports are one of the transportation nodes that function as connecting facilities with other regions to carry out trade activities and have an impact on economic growth. This research photographs the Baubau Ferry Port in the Green Port concept which is currently being intensified by the Government. This type of research is qualitative and takes informants who understand the concept of a Green Port in relation to trade systems and encouraging economic growth. This research found that the Baubau Ferry Port is very strategic and has a strategic and vital role in encouraging equitable development and improving the regional economy, especially in Baubau City and its surroundings. The indicators for Greenport-based ports are environmental and social indicators as well as financial and economic indicators that are running optimally. The indicators of the Port Operational Performance Aspect must be improved by carrying out port operational performance calculations according to existing regulations. The conclusion of this research is that the Baubau Ferry Port can be encouraged to apply the principles of a Green Port so that it will support it in carrying out its good function in encouraging trade and encouraging equitable development and regional economic growth.